Role of Informed Consent in a Decision-making on Participation in The Clinical Trial: Multicenter study in Russia “Face to Face” - O. I. Zvonareva; E. S. Kulikov; I. A. Deev; O. S. Kobyakova; O. S. Fedorova; N. A. Kirillova; E. A. Starovoytova; N. G. Zhukova; I. A. Zhukova; V. V. Esip; E. D. Schastnyy; N. V. Khurkhurova; et al. (Бюллетень сибирской медицины)
Introduction. Currently, clinical trials (CT) remain the only technology, which provides proof of efficacy and safety of new drugs and their subsequent release to the market. Medical researcher and informed consent (IC) are the main (and often the only) source of information for the patient about the upcoming clinical trials, and thus have a direct impact on the perception of clinical trials, and on the patient’s decision about participation. However, the degree of influence of these factors on the clinical trials participants still remains unclear.Materials and methods. A multicenter cross-sectional study was conducted in different cities of the Russian Federation. Patients who had previous experience in CTs (or were enrolled in a CT at the time of this study) were asked to complete a questionnaire.Results. To assess the impact of researcher, all respondents were divided into 2 groups: patients that acquainted with IC in collaboration with the researcher, and the other group, which reviewed IC form independently. We evaluated the importance of the factors influencing the decision-making process on participation in clinical trials. According to our data, the most important factors were professional monitoring services (3,72 ± 1,00), regular condition monitoring (3,66 ± 0,98), and better medical care (3,62 ± 1,00). These factors were evaluated at significantly lower score by group of patients that acquainted with IC together with the researcher (3,55 ±0,94, vs 4,01 ± 0,90, p = 0,002; 3,52 ± 1,01 vs 3,87 ± 0,90, p = 0,040; 3,49 ± 0,94, vs 3,83 ± 1,06, p = 0,020 respectively). In assessing the factors that had negative impact on the interest in participating in a clinical trial, the most significant were risk of side effects (3,01 ± 1,27), study of new medication (2,68 ± 1,21), and the risk of getting into the placebo group (2,64 ± 1,34) (so-called “objective” risk factors). At the same time, risk of side effects and risk of getting into the placebo group were also assessed at significantly lower score by group of patients that acquainted with IC together with the researcher (2,87 ± 1,28, vs 3,33 ± 1,17, p = 0,024; 2,51 ±1,25, vs 3,03 ± 1,34, p = 0,022 respectively). Furthermore, it was found that in the case of the researcher’s assistance acquaintance time with IC reduced threefold. We also evaluated the effect of the complexity of IC text on the decision-making process on participation in clinical trials. The group of respondents, who rated the IC as easy, appeared to be more interested in the final results of the study.Conclusion. Thus, when assessing the impact of the researcher on the review process of informed consent with the decision to participate in clinical trials, we found that in the case of assistance of the researcher, the acquaintance time with IC is reduced three times. In addition, this group of patients during the conversation with the researcher shows better and more clear understanding of the nature and general methodology of clinical trials, resulting in an adequate assessment “objective” risk factors for participation in clinical trials. Thus, this group of patients is more informed, compared with an “independent” group. According to the study “Face to Face”, we can recommend mandatory participation of a researcher during review process of the IC.